Data Challenges and Solutions in Energy‐for‐Water: Experience From Two Recent Studies. Issue 2 (4th February 2019) - Sowby, Robert B.; Burian, Steven J.; Chini, Christopher M.; Stillwell, Ashlynn S.
Abstract : Gathering utility‐specific energy data is challenging now, but unified data acquisition and management practices could close gaps in the energy–water nexus.